Party differences in political content on social media. Issue 5 (12th September 2016) - Vraga, Emily
Abstract : Purpose: Social networking sites (SNS) increasingly serve as a source of political content for Americans. The purpose of this paper is to clarify the relationships between types of political content exposure, especially congruent vs incongruent content, and its effects on political expression and participation. This study pays special attention to whether these relationships differ depending on whether an individual affiliates with the Republican or Democratic party. Design/methodology/approach: This study uses a representative national sample to examine the relationships among exposure to congruent vs incongruent political content via SNS, political expression, and political participation. This study also tests whether these relationships are consistent for Democrats vs Republicans. Findings: The results suggest the effects of political content exposure on political expression on SNS depend on how many friends post about politics, as well as whether that content is congruent or incongruent with one's political beliefs. Moreover, the relationship between exposure to congruent vs incongruent content, political expression, and political participation differs for Republicans and Democrats. Originality/value: This study highlights the need for researchers to take more care in distinguishing the type of and the audience for political content exposure via social media websites. Further, if the relationships between seeing political content via social media and acting upon such content – either through posting behaviors or participatory activities – differs by political group, it raises the potential for disparities in democratic engagement.